Consuming Life in Post-Bubble Japan : a Transdisciplinary Perspective. - Machotka, Ewa (Consumption and Sustainability in Asia Ser., 2018)
This multidisciplinary book analyzes the contradictory coexistence of consumerism and environmentalism in contemporary Japan. It focuses on the dilemma that the diffusion of the concepts of sustainability and recycling has posed for everyday consumption practices, and on how these concepts have affected, and were affected by, the production and consumption of art. Special attention is paid to the changes in consumption practices and environmental consciousness among the Japanese public that have occurred since the 1990s and in the aftermath of the earthquake, tsunami, and nuclear disasters of March 2011.